Gender-related morphological characteristics in preschool children of Kolubara district - Aleksandar Miletić; Branka Protić-Gava (University of Novi Sad, Faculty of Sport and Physical Education, 2017)
The aim of this study was to establish the gender-related differences among children 6-6.5 years of age in anthropometric characteristics so as to observe their development and make more appropriate selection for participation in guided and organised physical activities. A battery of 7 anthropometric measurements was used on the representative sample of 175 subjects of both genders from Valjevo (M=45 aged 6 and M=83 aged 6.5; F = 44 aged 6 and F=43 aged 6.5). The multivariate analysis of variance showed the existence of statistically significant differences (p=0.00) in the anthropometric space of the two ages analysed regarding the gender. Through the individual analysis, the differences at age 6 were found in the Upper arm skin fold variable (p=0.03) and the Back-skin fold (p=0.00), whereas with the 6.5-year-old subjects, the differences were found in the Body height variable (p=0.03), Upper arm skin fold (p=0.00) and Back skin fold (p=0.02), both in favour of the boys. It can be assumed that the differences are the result of the endogenous and exogenous factors upon the children's organism in the period of childhood in a smaller urban community of the southwest Serbia.